Meningkatkan Aktivitas Dan Hasil Belajar Siswa Materi Perubahan Wujud Benda Menggunakan Kombinasi Model Dari Problem Based Learning (PBL), Student Team Achievement Division (STAD) Dan Team Games Tournament (TGT) Pada Kelas V SDN Sungai Gampa Asahi Rantau - Siti Aisyah Ismi; Wahdah Refia Rafianti (Jurnal Pendidikan Sosial Dan Konseling, 2023)
The problem in this study is the low activity and learning outcomes of students in Natural Sciences (Science) learning. This is because learning is less interesting and meaningful, learning is still teacher-centered, and students are less accustomed to group learning. Efforts to overcome these problems are by applying the learning model Model Problem Based Learning (PBL), Studend Team Achievement Division (STAD) and Team Games Tournament (TGT) in learning. The purpose of this study is to describe teacher activity, analyze the increase in student activity, and learning outcomes. Qualitative and quantitative approaches. PTK is held in 3 meetings, class V of SDN Sungai Gampa Asahi Rantau Badauh, 20 students in 2022/2023. Qualitative data analysis techniques observation sheets teacher activities, and student activities while quantitative data measure learning outcomes. The results showed that teacher activity got 93%. Student activity gets 100%. Cognitive learning outcomes get 100%, affective get 100% and psychomotor get 100%. Based on the results of the study, the Problem Based Learning (PBL), Studend Team Achievement Division (STAD) and Team Games Tournament (TGT) models were concluded. can improve and learning outcomes. It is recommended that this model be used as an alternative to improve activity and learning outcomes.